EF24 Suppresses Cholangiocellular Carcinoma Progression, Inhibits STAT3 Phosphorylation, and Induces Apoptosis via ROS-Mediated Oxidative Stress. (4th March 2019) - Bisht, Savita; Nolting, Jens; Wenzel, Jörg; Brossart, Peter; Feldmann, Georg
Abstract : Therapeutic options for advanced stage cholangiocellular carcinoma (CCC) are very limited as of today and patients carry an exceptionally poor overall prognosis. In recent years, increasing evidence has been accumulated to suggest that malignant cells widely show increased intrinsic ROS levels and exhibit altered redox profiles as compared to normal counterparts, opening up potential avenues for therapeutic intervention. This study provides preclinical experimental evidence of therapeutic activity of the curcumin analog EF24 in cholangiocarcinoma models. In CCC cell lines, EF24 inhibited cell viability and induced apoptosis through excessive ROS generation. Moreover, administration of EF24 led to depletion of total intracellular GSH levels, induced mitochondrial depolarization, and abrogated STAT3 phosphorylation. Of interest, these effects were readily averted by treating the cells with exogenous antioxidants such as N-acetyl cysteine (NAC) or glutathione monoethyl ester (GEE). In vivo, EF24, solubilized using a cyclodextrin formulation, significantly suppressed the growth of tumor xenografts without exhibiting any toxic adverse effects. Immunohistochemical analysis of extracted tumor tissues demonstrated reduced nuclear staining for Ki-67 and downregulation of phospho-STAT3 as well as strong staining for oxidative stress biomarker 8-OHdG. Therefore, the data presented here suggest EF24 as potential therapeutic compound against CCC which might act at least to some extent through ROS-induced oxidative damage, subsequently inducing apoptosis. Further evaluation of this approach should be carried out in future follow-up studies.